Duration of the Third Stage of Labor and Risk of Postpartum Hemorrhage. Issue 5 (May 2016) - Frolova, Antonina I.; Stout, Molly J.; Tuuli, Methodius G.; López, Julia D.; Macones, George A.; Cahill, Alison G.
Abstract : OBJECTIVE: To characterize the duration of the third stage of labor and the association with postpartum hemorrhage in a contemporary cohort. METHODS: We performed a secondary analysis of a cohort of 7, 121 women who had a vaginal delivery at or beyond 37 weeks 0 days of gestation at a single tertiary care center from April 2010 to August 2014. Active management of the third stage of labor was routinely used during the study period. The mean, median, interquartile range, 90th percentile, 95th percentile, and 99th percentile of the third stage of labor duration were calculated. Odds ratios were calculated to estimate the association between increased duration of third stage of labor and incidence of postpartum hemorrhage. RESULTS: The mean duration of the third stage of labor among women who had a vaginal delivery was 5.46 (standard deviation 5.4) minutes and median duration was 4 minutes. The 90th, 95th, and 99th percentiles were defined by 9, 13, and 28 minutes, respectively. Women with a third stage above the 90th percentile (n=705) had an increased risk for postpartum hemorrhage compared with a third stage below the 90th percentile (13.2% compared with 8.3%; adjusted odds ratio [OR] 1.82, 95% confidence interval [CI] 1.43–2.31). When the 90th percentile was further subdivided into 5-minute increments, risk for postpartum hemorrhage significantly increased beginning at 20–24 minutes compared with shorter third-stage durations (15.9% compared with 8.5%; adjusted OR 2.38, 95% CI 1.18–4.79). However, blood transfusion was not associated with third-stage duration (1.0% compared with 0.84% for third-stage duration greater than 90th compared with 90th percentile or less, adjusted OR 1.18, 95% CI 0.53–2.60). CONCLUSION: Our data show that postpartum hemorrhage risk increases significantly when the third stage of labor duration is 20 minutes or more, suggesting that the definition of a prolonged third stage of labor being 30 minutes or more may be outdated. Abstract : Contemporary duration of the third stage of labor is shorter than previously thought.